An Alumina/Polyacrylonitrile Nanofibrous Composite Separator via High-Efficiency Electro-Blown Spinning and Wet-Laid Technologies for Improved Lithium-Ion Batteries. Issue 16 (1st January 2019) - Liu, Weicui; Wang, Liyuan; Luo, Yongsha; Wang, Gang; Li, Lei; Cheng, Bowen; Kang, Weimin; Ju, Jingge
Abstract : In this study, the alumina (Al2 O3 ) nanofibers and polyacrylonitrile (PAN) nanofibers are respectively prepared by the high-efficiency, low-cost and feasible electro-blown spinning (EBS) technology. Then, the nanofibrous composite membranes composed of Al2 O3 nanofibers and PAN nanofibers are manufactured via a simple and convenient wet-laid method for use as separator in lithium-ion batteries (LIBs). The results indicate that the novel nanofibrous composite membranes containing Al2 O3 nanofibers own excellent thermal stability, which can effectively improve the battery safety. Furthermore, it is found that, compared with pure PAN and commercial separators, the nanofibrous composite separators show higher porosity, better affinity for liquid electrolyte and lower interfacial resistance by introducing a high dosage of Al2 O3 nanofibers of 30 wt%, leading to superior C-rate capability and more stable cycling ability. In addition, the LIBs assembled with 30 wt% Al2 O3 /PAN separator exhibit high discharge specific capacity of 152.9 mAh/g at the current density of 0.5 C and possess high capacity retention of 83.1% after 200 cycles.